LITERATURE REVIEW: THE EFFECT OF TAXES ON THE GROWTH OF SMALL AND MEDIUM ENTERPRISES - Loso Judijanto; Abdul Wahab Syakhrani (Prosiding Seminar Nasional Indonesia, 2025)
SMEs are the backbone of the economy, but are often negatively impacted by undirected tax policies. In this study, the researcher used the literature research method. The results show that taxes have a significant influence on cash flow and capital availability, which directly affects the ability of SMEs to invest and grow. High tax rates and complex administrative processes are often a major obstacle to the growth of SMEs, reducing their competitiveness in the market, both locally and internationally. In addition, the importance of tax incentives as a policy tool that can encourage SME growth. Incentives in the form of tax deductions, duty exemptions, and simpler tax policies have proven effective in supporting SMEs to expand and increase productivity. Education and socialisation of tax policies are also identified as important factors in improving SMEs' understanding and compliance with tax regulations.